Association of Autoimmune Disorders and Disease-modifying Antirheumatic Drugs: (DMARDs) with the Risk of Alzheimer’s and/or Dementia: A Population Study Using Medicare Beneficiary Data - Ding, Qian; Lamberts, Jennifer; Konieczny, Alison M.; Bringedahl, Tyler B.; Torres Garcia, Kiara Y. (Current Alzheimer Research, 2023)
>Objectives: Alzheimer's disease (AD) and/or dementia is a prevalent neurocognitive disorder primarily affecting individuals over the age of 65. Identifying specific causes of AD and/or dementia can be challenging, with emerging evidence suggesting a potential association with autoimmune inflammatory conditions such as rheumatoid arthritis (RA). This study aimed to assess the prevalence rate of AD and/or dementia among Medicare beneficiaries reporting an autoimmune disorder. Additionally, this study sought to identify the comparative prevalence of AD and/or dementia in patients with an autoimmune disorder who were using disease-modifying antirheumatic drugs (DMARDs) compared to those not using DMARDs. Methods: Cross-sectional secondary data analyses were conducted on Medicare Current Beneficiary Survey (MCBS) data from 2017 and 2018. The MCBS data consists of a nationally representative sample of the Medicare population, a population that is largely 65 and older, and provides de-identified patient information. Patients from this dataset with a self-reported autoimmune disorder were included in the analyses. Descriptive analyses were conducted on demographic variables, chronic conditions, and medication use. The prevalence of AD and/or dementia was compared between patients with and without an autoimmune disorder. A backward stepwise selection regression was used to identify the risk factors associated with the prevalence of AD and/or dementia. Results: The study included 18,929 Medicare beneficiaries, with 4,405 identified as having one autoimmune disorder. The prevalence of AD and/or dementia was significantly higher in patients with an autoimmune disorder. The multivariate regression showed that RA was significantly associated with a higher risk of AD and/or dementia. Other demographic factors, including advanced age, African-American or Hispanic ethnicity, low body mass index, and chronic conditions of ischemic heart disease, history of myocardial infarction, history of stroke, depression, mental health disorder(s), and traumatic brain injury also showed statistically significant associations with AD and/or dementia. Patients using DMARDs demonstrated a reduced likelihood of having AD and/or dementia, compared to patients not using DMARDs. Conclusion: This study provides evidence of an association between RA and increased risk of AD and/or dementia. The findings suggest that DMARD use may have a protective effect against the development of AD and/or dementia in patients with an autoimmune disorder.
Keywords: Medicare Current Beneficiary Survey